Internet-based Design of Hydroponic Plants Monitoring and Automation Control Systems - Parenreng, Jumadi Mabe; Andani, Andi Ferry Adlian Tri; Yahya, Muhammad; Adiba, Fhatiah (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Melons are one of the fruit types widely favored in the market due to their high content of vitamins, minerals, and water. Melon plants are challenging to cultivate when environmental conditions such as soil and air do not align with their characteristics. One way to address this is through hydroponic cultivation, which reduces the interaction of melon fruits with the air and environment. However, this method has a drawback in that the nutrient solution and water circulation of the plants must be continuously monitored. Therefore, a system is needed to automatically monitor and control the conditions of hydroponic plant growth with the assistance of IoT technology. This research proposes the Design and Implementation of a Monitoring and Automation System for Hydroponic Plant Control Based on the Internet of Things. The hydroponic system, specially designed for melon plants, is equipped with various sensors that can monitor soil nutrients in real time through mobile devices. Based on the test results, the TDS sensor yielded a result of 1313 PPM, the pH Water sensor showed 50.1, and the system also measured air temperature and humidity using DHT22, with air temperature at 29.5°C and humidity at 71.2%.